The Use of Different Components of Brain Oxygenation for the Assessment of Cerebral Haemodynamics: A Prospective Observational Study on COVID-19 Patients - Robba, Chiara; Cardim, Danilo; Ball, Lorenzo; Battaglini, Denise; Dabrowski, Wojciech; Bassetti, Matteo; Giacobbe, Daniele Roberto; Czosnyka, Marek; Badenes, Rafael; Pelosi, Paolo; Matta, Basil; , The GeCovid group; et al. (Frontiers in Neurology, 2021)
Introduction: The role of near-infrared spectroscopy (NIRS) for the evaluation of cerebral haemodynamics is gaining increasing popularity because of its noninvasive nature. The aim of this study was to evaluate the role of the integral components of regional cerebral oxygenation (rSO2) measured by NIRS [i.e., arterial-oxyhemoglobin (O2Hbi) and venous-deoxyhemoglobin (HHbi)-components], as indirect surrogates of cerebral blood flow (CBF) in a cohort of critically ill patients with coronavirus disease 2019 (COVID-19). We compared these findings to the gold standard technique for noninvasive CBF assessment, Transcranial Doppler (TCD). Methods: Mechanically ventilated patients with COVID-19 admitted to the Intensive Care Unit (ICU) of Policlinico San Martino Hospital, Genova, Italy, who underwent multimodal neuromonitoring (including NIRS and TCD), were included. rSO2 and its components [relative changes in O2Hbi, HHbi, and total haemoglobin (cHbi)] were compared with TCD (cerebral blood flow velocity, CBFV). Changes (Δ) in CBFV and rSO2, ΔO2Hbi, ΔHHbi, and ΔcHbi after systemic arterial blood pressure (MAP) modifications induced by different manoeuvres (e.g., rescue therapies and haemodynamic manipulation) were assessed using mixed-effect linear regression analysis and repeated measures correlation coefficients. All values were normalised as percentage changes from the baseline (Δ%). Results: One hundred and four measurements from 25 patients were included. Significant effects of Δ%MAP on Δ%CBF were observed after rescue manoeuvres for CBFV, ΔcHbi, and ΔO2Hbi. The highest correlation was found between ΔCBFV and ΔΔO2Hbi (R = 0.88, p < 0.0001), and the poorest between ΔCBFV and ΔΔHHbi (R = 0.34, p = 0.002). Conclusions: ΔO2Hbi had the highest accuracy to assess CBF changes, reflecting its role as the main component for vasomotor response after changes in MAP. The use of indexes derived from the different components of rSO2 can be useful for the bedside evaluation of cerebral haemodynamics in mechanically ventilated patients with COVID-19.